IMPLEMENTASI VIDEO LIVE ACTION PADA PEMBUATAN VIDEO PEMBELAJARAN MERAKIT LAMPU ENERGI LISTRIK DARI BATERAI - Putra Prasetyo, Kevin Rafael; Hariyanto, Didik; Ciptaningtyas, Ariesta Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital learning technology requires effective innovation to support more concrete conceptual understanding, particularly in electricity topics at the elementary school level. Science (IPAS) learning on simple electrical circuits still requires tools that can clearly and systematically demonstrate experimental processes. This study aims to develop and determine the feasibility of a live-action instructional video entitled “Assembling an Electric Lamp Powered by a Battery” for fifth-grade elementary school students. The methodology employed was Research and Development (R&D) using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. Data were collected through observation, literature review, and validation questionnaires using a five-point Likert scale. The validation subjects consisted of three subject matter experts and three media experts. The data were analyzed by calculating the feasibility percentage based on the comparison between the obtained scores and the maximum possible scores. The results indicate that validation by subject-matter experts reached a feasibility percentage of 90%, categorized as highly feasible, while validation by media experts reached 95%, also categorized as highly feasible. The aspects of scientific accuracy, language use, and media integration received excellent evaluations, although there were suggestions for improving the clarity of alignment between the content and the learning objectives. Therefore, the developed live-action instructional video is considered feasible for use as a learning medium in elementary science (IPAS) on basic electricity and has the potential to enhance conceptual understanding through authentic and direct demonstrations.